Theoretical and methodological principles in development of art education - Sayapina, Nataliya N.; Al-Jazaeri, Mohammed K. (Saratov State University, 2023)
The study appears relevant due to the need of theoretical and applied pedagogy to research the issues of art education concerning its theoretical and methodological aspects. The purpose of the research is to study the theoretical and methodological principles in development of art education. Attention is drawn to the content of the Art Education Framework as a federal-level document that develops the strategy of the cultural policy of the Russian Federation in the designated area and regulates art education in educational organizations of diff erent levels. Research results. It is shown that the creation of art education theories is a rather complex process which makes scholars consider basic scientific theories: the theory of artistic perception and the theory of artistic creativity, which are regarded through their applied aspect. Our interest in visual fi ne art determines the prerequisite of considering the theories of visual fi ne arts in various historical periods. These theories serve as a theoretical basis both in the fi eld of art education and in the fi eld of fi ne arts. The article summarizes the main movements in teaching fi ne arts at school created by various authors. The article emphasizes that the study of both these movements and the fi ne arts educational programs that correspond to them facilitate the choice in favor of the program that would fi t the curriculum of a particular educational organization. The idea of what results of students’ visual arts development should be is refl ected in both the concepts and methods of fi ne arts education that are presented in the program an educational organization will choose. These results become the methodological basis in development of art education. Main conclusions: the article emphasizes the necessity to carry out theoretical and methodological research in the fi eld of art education as well as to overcome the problems of creating “coherent” theories of art education, theories of visual fi ne art and methods of teaching it based on the experience accumulated by Russian and foreign theorists and practitioners.